The Application of Nanomaterials in Angiogenesis - Li, Tianle; Zhang, Tao (Current Stem Cell Research & Therapy, 2021)
Induction of angiogenesis has enormous potential in the treatment of ischemic diseases and the promotion of bulk tissue regeneration. However, the poor activity of angiogenic cells and proangiogenic factors after transplantation is the main problem that imposes its wide applications. Recent studies have found that the development of nanomaterials has solved this problem to some extent. Nanomaterials can be mainly classified into inorganic nanomaterials represented by metals, metal oxides and metal hydroxides, and organic nanomaterials including DNA tetrahedrons, graphene, graphene oxide, and carbon nanotubes. These nanomaterials can induce the release of angiogenic factors either directly or indirectly, thereby initiating a series of signaling pathways to induce angiogenesis. Moreover, appropriate surface modifications of nanomaterial facilitate a variety of functions, such as enhancing its biocompatibility and biostability. In clinical applications, nanomaterials can promote the proliferation and differentiation of endothelial cells or mesenchymal stem cells, thereby promoting the migration of hemangioblast cells to form new blood vessels. This review outlines the role of nanomaterials in angiogenesis and is intended to provide new insights into the clinical treatment of systemic and ischemic diseases.
Keywords: angiogenesis